The Usage of 'Otsukare' among Japanese Students - Santiar, Lea; Dewangga, Jascha (Chi'e: Journal of Japanese Learning and Teaching, 2021)
Greetings are one of the keys to strike a conversation. The relationship between the speakers could be measured through the greetings used. Therefore understanding greeting usage is necessary for maintaining an interpersonal relationship. Nevertheless, there seems to be a difference between greetings thought within Japanese textbooks and greetings in daily usage. Thus, this study will discuss the usage of ‘otsukare’ in Japan, especially amongst Japanese university students. The textbook "Minna no Nihongo" will be used to comprehend how aisatsu is taught to Japanese language learners. In this research, Japanese university students will answer a questioner regarding the usage of ‘otsukare’. A questionnaire was designed based on sociolinguistics concepts to discover how Japanese university students use ‘otsukare’, such as when to whom, and in what manner. 40 university students of native Japanese participated and as the result, four points were discovered regarding the usage of ‘otsukare’ First, ‘otsukare’ is used to greet seniors, juniors, and friends. Second, native Japanese speakers prefer to use ‘otsukare’ on departing. Third, nevertheless, some people also use ‘otsukare’ to greet people as an opening greeting. Native Japanese speakers consider the usage of ‘otsukare’ in the morning as opening greetings is not against the rule of greetings. Finally, the gap between Japanese teaching abroad is that ‘otsukare’ is not proper to be used as an opening greeting.